Study on the improvement of image interpretation skill of non-radiology residents based on an image case database in gastroenterology department - Xiayin He; Yangsheng Li; Chengcheng Gao; Xiangwen Zhu; Qianqian Xia; Zhijiang Han; Jiying Zhu (BMC Medical Education)
Abstract Background Medical imaging plays a very important role in the diagnosis, treatment and prognosis of digestive diseases. This manuscript aimed to explore the value of a teaching model based on an image case database in improving the image interpretation skills of non-radiology residents training in gastroenterology department. Methods From October 2023 to March 2024, all the residents training in the gastroenterology department were selected as the research subjects. Using the implementation date of the teaching model based on an image case database as the cutoff point, the experimental group comprised 27 residents (January–March 2024), while the control group included 24 (October–December 2023). The experimental group learned by using a teaching mode based on an image case database, whereas the control group learned by using conventional teaching methods. The effects of the two teaching modes were evaluated through the examination of admission, mid-term and exit performance scores, and questionnaires were used to feedback the evaluation of the residents of the experimental group on the teaching mode of the case database. Results The scores of non-radiology residents in the experimental group and the control group showed no difference in the admission examination ( P = 0.728), but the scores in the experimental group were significantly higher than those in the control group at the mid-term (P = 0.006) and exit examination (P = 0.002), respectively. In the experimental group, 100% (27/27) of the residents believed that radiology was very important for the mastery of clinical knowledge in gastroenterology, 88.9% (24/27) of these residents believed that the teaching mode significantly improved their image interpretation skills and interest in using images to learn, and 81.5% (22/27) were very willing to accept the teaching mode of image case database in other clinical departments. Conclusion The teaching mode based on an image case database could improve the image interpretation skills of non-radiology residents training in the gastroenterology department, and could be popularized in more departments for residents training.